(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
The paper dwells on the analysis of the stylistic problem of educational work in the context of the project paradigm. The author examines the content and effectiveness of educational work style. Moreover, the author examines factors that have an influence on educational work style. The paper elucidates the results of empirical research of students’ educational work style.